Time course of changes in the level of N-terminal pro-brain natriuretic peptide (NT-proBNP) in patients with rheumatoid arthritis during therapy with an interleukin-6 receptor inhibitor - E. V. Gerasimova; T. V. Popkova; A. V. Martynova; M. V. Cherkasova; D. S. Novikova (Научно-практическая ревматология, 2019)
Objective: to investigate the impact of therapy with the interleukin-6 receptor inhibitor tocilizumab (TCZ) on the time course of changes in N-terminal pro-brain  natriuretic  peptide (NT-proBNP) levels in patients with rheumatoid arthritis (RA) during a 12-month follow-up period.Subjects and methods. 31 RA patients (26 women and 5 men) with an inadequate  response and/or intolerance  to disease-modifying antirheumatic drugs (DMARDs) were included. Their median age was 54 [45; 61] years; the disease duration – 110 [62; 168] months; DAS28 – 6.2 [5.1; 7.1]; SDAI – 35.0 [23.9; 51.0], and CDAI – 30.0 [21.0; 42.0]. All the patients were seropositive for rheumatoid  factor (RF),  84% – for anti-cyclic citrulinated  peptide (anti-CCP) antibodies. Extra-articular manifestations were found in 54% of patients. Patients with chronic heart failure were notincluded. The RA patients were found to have a high frequency of traditional  risk factors for cardiovascular diseases (CVD): hypertension  (75%), dyslipidemia (61%), smoking (17%), overweight (61%), a family history of CVD (36%), and hypodynamia (68%). Coronary heart disease was diagnosed in 11% of patients. The inefficacy of three or more NSAIDs was noted in 45% of cases; intolerance  to previous therapy with NSAIDs was observed in 55%. The patients received TCZ at a dose of 8 mg/kg every 4 weeks: 39% received TCZ alone; 61% – in combination  with methotrexate (MTX), the MTX median dose was 20 [18; 25] mg/week. The level of NT-proBNP was measured before and 12 months after TCZ therapy.Results and discussion. After 12 months of treatment with TCZ 54% of patients had disease remission (DAS28 <2.6), 46% – low disease activity (DAS28 <3.2). Median DAS28 value decreased from 6.2 [5.1; 7.1] to 2.7 [1.5; 3.3] (p<0.01), erythrocyte sedimentation rate (ESR) – from 38 [24; 54] to 8 [4; 16] mm/h (p<0.01), C-reactive  protein (CRP)  – from 27 [10; 49] to 0.5 [0.2; 0.7] mg/L (p<0.01) and NT-proBNP – from 75.8 [43.0; 100.7] to 37.8 [25.1; 78.5] pg/l (p=0.01), although the frequency of its increased values (≥100 pg/ml)  remained unchanged  (13%). There was a correlation of ΔNT-proBNP with ΔESR (r=0.43;  p<0.05) and with ΔCRP (r=0.46;  p<0.05). No association was found between ΔNT-proBNP, RA activity measures, RF, and anti-CCP. The level of NT-proBNP in patients treated with TCZ alone and in combination  with MTX did not differ considerably.Conclusion. After 12 months of treatment to suppress RA activity, there was a decrease in NT-proBNP levels when TCZ was used alone and in combination with MTX. The lower concentration of NT-proBNP was associated with a reduction  in acute phase measures (CRP and ESR). Control  of RA activity results in the reduced damaging effect of inflammation on the myocardium.